Disekuilibrium Kebijakan Transportasi Konvensional Dengan Transportasi Online Di Tangerang Selatan - Djoni Gunanto; Muhammad Amin Tohari; Nur Muhamad Iqbal (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2022)
Public policy is an alternative carried out by the government in dealing with problems that occur in society. The provision of public transportation services by the government with online transportation service providers still causes disquilibrium in the process of implementing public policy. PM 15 of 2019 with PM 118 of 2018 as a policy that regulates public transportation occurs disquilibrium in the policy, the existence of online transportation providing public transportation services finds losses on driver income and Regional Native Income as a public transportation levy, KIR test as a treatment of public transportation and a form of government supervision does not occur in online transportation, Vehicle storage facilities do not have to be owned by online transportation compared to must-have public/conventional transportation and vehicle maintenance and repair. From the various approaches that are widely proposed by many experts, this research will combine the tools of successful public policy implementation, namely 1) Communication 2) Goals 3) Program Implementation, 4) Implementation Context, 5) Compliance and Response. Qualitative research method with a descriptive approach with data collection techniques carried out through field observation, interviews and documentation. The result is that the transportation policy has a disquilibirum on one transportation service where the transportation manager has a difference of view between public services and profits, therefore disquilibriumbecomes evident in the implementation of the policy. In conclusion, the general transportation policy has its own goals in regulating driver operations, not in the transportation service manager